Analysis of Improving the Quality of Mass Transportation Services with the Buy the Service (BTS) Scheme Using the Importance Performance Analysis (IPA) Method: Case Study of BTS Route Gresik – Lamongan - Alfianti, Diah Mega; Tjendani, Hani Teki; Witjaksana, Budi (Journal of World Science, 2025)
Transportation is fundamental to societal function, impacting lifestyles, production, and service accessibility, and it is a cornerstone of urban mobility. This study evaluates the quality of mass transportation services under the Buy The Service (BTS) scheme on the Gresik - Lamongan route using Importance-Performance Analysis (IPA). The research identifies key performance attributes influencing passenger satisfaction using primary data from field observations, passenger surveys, and secondary data from local transportation authorities. Results indicate high satisfaction with safety features like fire extinguishers, glass breaker hammers, and accessibility features such as priority seating for wheelchair users. However, improvements are needed in areas such as bus intervals and operational consistency. The IPA quadrant analysis highlights strategic priorities for enhancing service quality. Recommendations include prioritizing safety, optimizing accessibility, and leveraging technology to improve reliability and efficiency. These findings offer policymakers and transportation operators insights to enhance service delivery and meet diverse passenger needs.